2021
DOI: 10.1371/journal.pone.0258780
|View full text |Cite
|
Sign up to set email alerts
|

Scabies in Spain? A comprehensive epidemiological picture

Abstract: Introduction Scabies is a neglected disease stablished worldwide with a fairy well determined incidence. In high-income countries, it often causes outbreaks affecting the residents and staff of institutions and long-term facilities, usually hard to detect and control due to the difficult diagnosis and notification delay. This study aim at characterizing the affected population, geographical distribution, and evolution of scabies in Spain from 1997–2019 as well as to describe the main environments of transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The observed increase in incidence corresponds with the trend in other European countries, such as Germany, Norway, Croatia, Poland, and Spain [1][2][3][4]11]. Although each country has slightly different surveillance systems in place or used other data sources than our study, they all still reported an increase in the last years.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The observed increase in incidence corresponds with the trend in other European countries, such as Germany, Norway, Croatia, Poland, and Spain [1][2][3][4]11]. Although each country has slightly different surveillance systems in place or used other data sources than our study, they all still reported an increase in the last years.…”
Section: Discussionsupporting
confidence: 80%
“…The increasing trends were most striking in adolescents and (young) adults and was also timed roughly similarly. It is remarkable that these countries observed a comparable seasonal trend in autumn and winter season [1][2][3][4]11,12]. It can be suggested that the seasonal trend is caused by more contact during cold and dry seasons [12].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, scabies outbreaks have been reported in many countries [17][18][19][20]. In a study conducted in distinct geographic regions of Turkey, a 7-fold increase was found comparing 2017 and 2018, and a 30-fold increase was found and 2017 and 2019 [4].…”
Section: Discussionmentioning
confidence: 99%